2021
DOI: 10.3390/met11081320
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pure Pd(II) from Spent Electroplating Solutions by Solvent Extraction with Ionic Liquids from Sulfuric Acid Leaching Solution of Cemented Pd

Abstract: Palladium (Pd) electroplating is widely practiced in the manufacture of advanced electronic devices. The Pd(II) present in spent electroplating solutions is treated by cementation with zinc (Zn) metal powder. In order to recover pure Pd from the cemented Pd, a process that consisted of leaching followed by solvent extraction was investigated. For this purpose, solvent extraction experiments using synthesized ionic liquids (ILs) with organic and inorganic anions were performed to find separation conditions at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In order to increase the recovery percentage of Pd from the spent electroplating solutions, excess amount of zinc metal is employed in the cementation of Pd(II). Therefore, the concentration of Pd(II) and Zn(II) in the leaching solution would depend on the composition of the cemented Pd and leaching conditions (Song et al, 2021;Nguyen et al, 2021). In this study, the concentration of Pd(II) and Zn(II) in synthetic HCl leaching solution was kept at 100 and 500 mg/L, respectively.…”
Section: Effect Of Hcl Concentration On the Separation Of Pd(ii) Over Zn(ii)mentioning
confidence: 98%
See 3 more Smart Citations
“…In order to increase the recovery percentage of Pd from the spent electroplating solutions, excess amount of zinc metal is employed in the cementation of Pd(II). Therefore, the concentration of Pd(II) and Zn(II) in the leaching solution would depend on the composition of the cemented Pd and leaching conditions (Song et al, 2021;Nguyen et al, 2021). In this study, the concentration of Pd(II) and Zn(II) in synthetic HCl leaching solution was kept at 100 and 500 mg/L, respectively.…”
Section: Effect Of Hcl Concentration On the Separation Of Pd(ii) Over Zn(ii)mentioning
confidence: 98%
“…Our previous work showed that the complete leaching of Pd and Zn was obtained by employing the mixture of 9 M HCl in presence of 0.5% (v/v) H2O2 at 60 o C for 60 min (Nguyen et al, 2021). At this condition, the Pd and Zn metal in the cemented Pd were completely dissolved.…”
Section: The Separation Of Pd(ii) Over Zn(ii) From Real Hcl Leaching Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hydrometallurgical process, the target elements present in the secondary resources are dissolved by either inorganic or organic acid solutions. Since the leaching solutions contain not only the target metal ions but also some impure elements, these impure elements should be separated from the leaching solution by employing some unit operations like solvent extraction, ion exchange and precipitation [6][7][8]. In developing a process, it is necessary to find one which can meet both recovery efficiency and minimization of environmental burden.…”
Section: Introductionmentioning
confidence: 99%